Survey on examining prevalence of paternal anxiety and its risk factors in perinatal period in Hong Kong: a longitudinal study. (December 2015) - Koh, Y.W.; Lee, A.M.; Chan, C.Y.; Fong, D.Y.; Lee, C.P.; Leung, K.Y.; Tang, C.S.
Abstract Background There is emerging evidence of the significance of paternal mental health problems among the expectant fathers during the antenatal and postnatal period. The present study aims at determining the prevalence of paternal perinatal anxiety and identifying its risk factors among the fathers. Methods A total of 622 expectant fathers were recruited in Hong Kong. The expectant fathers were assessed using standardized and validated psychological instruments on three time points including early pregnancy, late pregnancy and 6 week postnatal. Independent samplest -test, one way ANOVA, Pearson's correlation and multiple linear regression were used to examine the effect of hypothesized risk factors. Hierarchical multiple regression and mixed effect model were also conducted with potential confounding factors controlled for. Results Results showed that a significant proportion of expectant fathers experienced anxiety during the perinatal period. Low self-esteem and poor social support were found to be risk factors of paternal anxiety across pregnancy to postnatal period. Work-family conflict could significantly predict paternal anxiety in the pregnancy period. Conclusions The present study points to the need for greater research and clinical attention to paternal anxiety, given that it is a highly prevalent problem and could be detrimental to their partner's well-being and children development. The present findings contributes to the theoretical understanding of the prevalence and risk factors of paternal perinatal anxiety and have implications for the design of effective identification, prevention, and interventions of these clinical problems.